PENEGAKAN HUKUM TERHADAP KEJAHATAN PERDAGANGAN ANAK DI BAWAH UMUR - Suzanalisa Suzanalisa (Universitas Batanghari Jambi, 2014)
Trafficking of minors is a legal issue that requires serious attention. Despite efforts to prevent crime prevention has been done, but had not been optimal to prevent and suppress crime rate is getting smaller, the opposite case is revealed through the data it can be seen that the crime rate is getting higher every year. Prevention efforts through policies without the support of specific regulations governing the trafficking of minors has shown that the legal issues in this area is handled in a way that is not serious. So it is to know the law enforcement against trafficking minors in the Criminal Code, outside the Criminal Code, and according to the Human Rights Act and the constraints faced by law enforcement against trafficking in minorsKeywords: Trade and Law Enforcement